Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1002/jnr.20559
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of acute and subchronic administration on phencyclidine‐induced neurodegeneration in the perinatal rat

Abstract: Acute and subchronic administration of N-methyl-D-aspartate antagonists to rats in the early postnatal period has been reported to produce widespread and selectively cortical neurotoxicity, respectively. To resolve this apparent discrepancy, we sought to clarify these data by determining the dose and temporal and regional characteristics of acute and subchronic phencyclidine (PCP)-induced neurotoxicity. Measurement of degenerating neurons with the cupric silver technique following a single dose of PCP on postn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 30 publications
2
31
0
Order By: Relevance
“…Sub-PCP administration to rodents, followed by a washout period, has been shown to affect hippocampal and fronto-cortical areas, thereby establishing a hypofunction of the prefrontal cortex resembling some aspects of schizophrenia pathology (Cochran et al 2003). Correspondingly, early postnatal treatment of rats with PCP has been proposed as a neurodevelopmental model of schizophrenia (Wang et al 2001) as this treatment paradigm produces widespread neurodegeneration in brain areas relevant to the cognitive deficits observed in schizophrenia patients, such as the hippocampus and frontal cortex (Ikonomidou et al 1999;Wang and Johnson 2005). As performance in the ID/ED task relies heavily on fronto-cortical processing (Birrell and Brown 2000), such a mechanistic theory could be applied to the positive effects of RO4938581 on neo-PCP-induced deficits seen here.…”
Section: Discussionmentioning
confidence: 97%
“…Sub-PCP administration to rodents, followed by a washout period, has been shown to affect hippocampal and fronto-cortical areas, thereby establishing a hypofunction of the prefrontal cortex resembling some aspects of schizophrenia pathology (Cochran et al 2003). Correspondingly, early postnatal treatment of rats with PCP has been proposed as a neurodevelopmental model of schizophrenia (Wang et al 2001) as this treatment paradigm produces widespread neurodegeneration in brain areas relevant to the cognitive deficits observed in schizophrenia patients, such as the hippocampus and frontal cortex (Ikonomidou et al 1999;Wang and Johnson 2005). As performance in the ID/ED task relies heavily on fronto-cortical processing (Birrell and Brown 2000), such a mechanistic theory could be applied to the positive effects of RO4938581 on neo-PCP-induced deficits seen here.…”
Section: Discussionmentioning
confidence: 97%
“…Increased glutamatergic stimulation also may produce excitotoxic neuronal effects (Danbolt, 2001) that could compromise cognitive function. Indeed, elevated glutamine levels or glutamine/glutamate ratios have been observed with other abused drugs such as ketamine (Rowland et al, 2005), phencyclidine (Iltis et al, 2009), and amphetamine (Pereira et al, 2008), which can induce neurotoxicity in animals (Green and Cote, 2009; Wang and Johnson, 2005) and humans (Jeong et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Nakatani-Pawlak et al (2009) reported that the impairment of social interaction behaviour following neonatal PCP was significantly reversed by administration of clozapine. Neonatal administration of PCP or MK-801 in rodents has been reported to decrease parvalbumin-positive cells and spine density, (Wang and Johnson, 2005;Nakatani-Pawlak et al, 2009), both of which have been reported in schizophrenia (Beneyto and Lewis, 2011). Neonatal NMDAR antagonists have been shown to cause deficits in attentional set shifting (Broberg et al, 2008), novelty discrimination (Terranova et al, 2005;Harich et al, 2007;Pichat et al, 2007;Boulay et al, 2008), reversal and spatial working memory tasks in the Morris water maze, and in the delayed-non-match-to-position task (Kawabe and Miyamoto, 2008).…”
Section: Prenatal Perinatal and Adolescent Administration Of Nmdar Amentioning
confidence: 96%